Impact of High-Pressure Homogenization on the Extractability and Stability of Phytochemicals - Yong, Shireena Xhiang Mun; Song, Cher Pin; Choo, Wee Sim (Frontiers in Sustainable Food Systems, 2021)
High-pressure homogenization (HPH) and high-pressure processing (HPP) are emerging technologies for the food industry. Both technologies employ high pressure to preserve foods. However, the principal mechanism of HPH is based on shear stress distribution in a material instead of a decrease in volume due to an increase in pressure as occurring in HPP. HPH can be used in extraction or preservation of bioactive compounds and phytochemicals. This review first describes the mechanism of HPH processing. Next, this review discusses the impact of HPH on extractability and stability of phytochemicals such as carotenoids, vitamin C, polyphenols, and anthocyanins in various food matrices. In general, the use of HPH slightly improved or maintained the extractability of the phytochemicals. Similarly, HPH slightly reduced or maintained the stability of the phytochemicals but this is dependent on the food matrix and type of phytochemical. HPH has a great potential to be used to improve the extractability and maintaining the stability of these phytochemicals or to be used together with milder thermal processing. Besides understanding the impact of HPH on the extractability and stability of phytochemicals, the impact of HPH on the nutritional quality of the food matrices needs to be thoroughly evaluated.